Estudio comparativo de las consecuencias en la economía luego de una externalidad negativa. Caso Japón y Haití. (2024)
Negative externalities, looking from the point of view of a natural catastrophe, are an event in which no country is exempt from going through it, hence the importance of differentiating the economic and political measures taken by countries who have had to go through this crisis, in this case the countries selected for this analysis are Japan and Haiti, we choose a developed country and one classified as a less developed country, because in this way we can focus on several characteristics, which help us unify a idea about measures that could work regardless of the socioeconomic level of the country that is affected in the future. In this research you will find a description of the main indicators of each of the countries, over time, to be able to observe their behavior and how Japan positions itself as a world power over the years, while Haiti remains in constant stagnation. showing a social and economic context that leads them to then face the earthquakes that each of them experienced. Projections were made in some sectors to observe what an initial behavior should have been like, had they not suffered the externality, to contrast them with the real data that the indicators give us, in this way, to be able to define whether the measures taken by each of the countries were effective, sectorally, or on the contrary, a change was not seen, thus bringing together the most important policies that led to a recovery, or that did not allow it.